The unemployment impact of the COVID-19 shutdown measures in Germany - Anja Bauer; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
This paper evaluates the short-term labour market impact of the COVID-19 Containment measures in Germany. We take the closure of economic sectors such as restaurants and retail as a treatment, which enables difference-in-difference estimation. Additionally considering input-output linkages between the sectors, we find that 60 percent of the considerably increased inflows from employment into unemployment in April 2020 were due to the containment measures. In a second approach, we make use of the fact that sector closures and curfews were implemented at different times by the German state governments. In a regional regression setup based on treatment intensity, we find that the hiring margin accounted for additional 82 percent of the unemployment effect coming from the separations margin. In sum, the lockdown measures increased unemployment in the short run by 117,000 persons. – – Wir analysieren die kurzfristigen Arbeitsmarkteffekte der COVID-19 Eindämmungsmaßnahmen in Deutschland. Mittels eines Differenzen-von-Differenzen Ansatzes, der auch die Verflechtung der Branchen über eine Input-Output Systematik berücksichtigt, zeigen wir, dass 60 Prozent der zusätzlichen Zugänge in Arbeitslosigkeit aus Beschäftigung zwischen März und April 2020 durch die Eindämmungsmaßnahmen erklärt werden können. In einem weiteren Ansatz nutzen wir die zeitliche Variation in der Einführung von Branchenschließungen und Ausgangsbeschränkungen in den Bundesländern. Eine regionale Regression zeigt, dass unterlassene Einstellungen rund 82 Prozent der Wirkung vermehrter Zugänge in Arbeitslosigkeit ausmachen und dadurch die Arbeitslosigkeit zusätzlich erhöhen. Insgesamt haben die Eindämmungsmaßnahmen kurzfristig zu einer Zunahme der Arbeitslosigkeit um 117.000 Personen geführt.
Keywords: J06; E24; 330; COVID-19; treatment effect; unemployment